CREATIVE TASKS FOR CHILDREN (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
This study investigates the effectiveness of various educational approaches in fostering creativity among children aged 5-12. It examines the impact of different teaching methods, learning environments, and types of creative tasks on children's cognitive development, problem-solving skills, and innovative thinking. The research employs a mixed-methods approach, combining quantitative data from standardized creativity assessments with qualitative data from classroom observations and teacher interviews. The findings reveal significant differences in the outcomes of different approaches, highlighting the importance of incorporating play-based learning, open-ended activities, and opportunities for self-expression. The study concludes with recommendations for educators and policymakers seeking to cultivate creativity in children and prepare them for the challenges of the 21st century.